A Study On The Purity And Recovery Of Carbon Dioxide Gas From Binary Flue Gas Mixture Using Different Adsorbents In Pressure Equalized Pressure Swingadsorptio - Rajalingam, Tharveen Raj (Universiti Sains Malaysia, 2017)
Carbon dioxide (CO2) gas emission to the atmosphere contributes to global warming and climate changes processes. To mitigate the effects of carbon dioxide release to the atmosphere, this study explores the usage of activated palm kernel shell adsorbent (APKS) and zeolitic imidazolate framework-8 (ZIF-8) in pressure swing adsorption (PSA) processes to remove carbon dioxide from a binary mixture of flue gas containing CO2 and nitrogen (N2) gas. CO2 is the more strongly adsorbed species compared to nitrogen in a flue gas. The adsorbents were both prepared and characterized using Brunauer–Emmett–Teller (BET) Analysis, Scanning Electron Microscope (SEM) analysis, Energy Dispersive X-Ray (EDX) analysis, Thermogravimetric analysis (TGA), Particle Size Analysis and X-Ray Diffraction (XRD) analysis. Breakthrough studies were performed on the adsorbents with the effect of adsorbent types and feed gas composition (15% - 25% CO2) investigated. APKS proved to be a better adsorbent with larger breakthroughs at the tested feed CO2 concentrations. The breakthrough time was adopted into the PSA and the performance of both adsorbents in the process were evaluated. The effects of adsorbent type and feed gas composition in PSA were investigated. The purity of carbon dioxide gas was able to be concentrated to 82.99% and a recovery of 99.61% was also determined. These results provide some promising insight into the application of APKS and ZIF-8 in carbon dioxide capture in PSA which could be useful for environmental remediation and nitrogen purification.